ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI UMKM - Putra, Putu Ryan Pramana; Hardika, Nyoman Sentosa; Suarjana, Anak Agung Gde Mantra (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2024)
The purpose of the study was to analyze: (1) The influence of digitalization of the tax system on taxpayer compliance, (2) The influence of taxpayer understanding on taxpayer compliance, (3) The influence of taxpayer awareness on taxpayer compliance, (4) The influence of digitalization of the tax system, understanding of taxes, and simultaneous taxpayer awareness on small micro business (SMEs) individual taxpayer compliance. Data was collected using questionnaires and documentation. The population studied was all SMEs individual taxpayers registered at the East Denpasar Pratama Tax Service Office. The sample was taken from 100 taxpayers using the Slovin formula with convenience sampling technique. The data analysis technique is the Partial Least Square technique at a significance level of 5%. The research results show that (1) Digitalization of the tax system has a positive and significant effect on taxpayer compliance, (2) Taxpayer understanding has a positive and significant effect on taxpayer compliance, (3) Taxpayer awareness has a positive and significant effect on taxpayer compliance, (4) Digitalization of the tax system, tax understanding, and taxpayer awareness simultaneously have a positive and significant effect on SMEs individual taxpayer compliance.